Compared between Experimental and numerical Study of Flat Slab that have Opening adjacent to Column with Embedded Shear Collar (Eurasian Journal of Engineering and Technology, 2023)
This study presents an experimental study and numerical study (ABAQUS program) of flat slab which has openings adjacent to the column by using several types of collar shear reinforcement to demonstrate its effect on the behavior of flat slab to resist piercing shear. Where the shear reinforcement is considered one of the important solutions to increase the resistance of the slabs to the failure of the punching shear and it is also possible through the use of these collars to provide service openings next to the columns. This research includes testing seven models of slabs with dimensions (1000 x 1000 x 75 mm), each slab contains a column with dimensions ( 200 x 200 x 150 mm) in the center of each slab. Reference model didn’t have opening and without collar, another model have opening and without using collar and five models contain openings adjacent to the column, as well as various shapes of shear collars, The results showed that the presence of openings led to a change in the behavior of the slabs, as well as the use of shear collars leads to an improvement in the behavior of the slabs compared to the model that contains an opening and does not contain shear collars. Where the presence of the openings adjacent to the column led to a ultimate load loss of (27%) and the use of these shear collars leads to reducing the ultimate load loss to (4-24%), depending on the type of collar used. Where The percentages of differences between the experimental results and the numerical results of the greatest pregnancy range from (2.1 – 10.2) %